UV–Vis and fluorimetric Al3+, Zn2+, Cd2+ and Pb2+ complexation studies of two 3-hydroxyflavones and a 3-hydroxythioflavone - Valente, J.; Buntine, Mark; Lincoln, S.; Ward, D. (Elsevier, 2007)
The complexation of Al3+, Zn2+, Cd2+ and Pb2+ by the 3-hydroxyflavones: 3-hydroxy-2-(2-methoxyphenyl)-4H-1-benzopyran-4-one (H1) and 3-hydroxy-2-(4-methoxyphenyl)-4H-1-benzopyran-4-one (H2), and by the 3-methoxythioflavone: 3-hydroxy-2-(2-methoxyphenyl)-4H-1-benzopyran-4-thione (H3) have been studied spectrophotometrically and fluorimetrically to determine the corresponding complexation constants, Ksp and Kfl, in 5:95 water:ethanol (v/v) solution for which [HClO4] was either 10-2 or 10-5 mol dm-3 and I = 0.10 mol dm-3 (NaClO4) at 298.2 K. Complexation occurs dominantly through the deprotonated ligand for [Al(1)]2+ and [Al(2)]2+ for which log Ksp = 4.51 and 4.73, respectively, in 10-2 mol dm-3 HClO4 and 4.21 and 4.61 in 10-5 mol dm-3 HClO4. For Pb2+ complexation by H1, H2 and H3 is characterized by log Ksp = 2.20, 2.57 and 3.22, respectively, in 10-2 mol dm-3 HClO4 and 4.70, 5.38 and 5.74 in 10-5 mol dm-3 HClO4. Equilibrium mixtures of [Pb(H1)]2+ and [Pb1]+, [Pb(H2)]2+ and [Pb2]+, and [Pb(H3)]2+ and [Pb3]+ appear to be formed. Complexation of Zn2+ and Cd2+ by all three ligands was only detected in 10-5 mol dm-3 HClO4. For Zn2+ complexation by H1, H2 and H3 log Ksp = 3.22, 3.74 and 4.46 and for Cd2+ the corresponding values are 2.39, 2.40 and 3.72 for Cd2+. Only [Al1]2+ and [Al2]2+ show significant fluorescence and are characterized by log Kfl = 6.30 and 7.49 in 10-2 mol dm-3 HClO4.